Autocrine Sonic hedgehog signaling promotes gastric cancer proliferation through induction of phospholipase Cγ1 and the ERK1/2 pathway. Issue 1 (December 2016) - Ertao, Zhai; Jianhui, Chen; Chuangqi, Chen; Changjiang, Qin; Sile, Chen; Yulong, He; Hui, Wu; Shirong, Cai
Abstract Background Sonic hedgehog (SHH) plays critical roles in cell growth and development. Tumor cells express SHH, which can promote cell proliferation and epithelial-to-mesenchymal transition. However, the autocrine SHH pathway has not been described in gastric cancer. The aim of this study was to explore molecular mechanisms underlying autocrine SHH signaling in gastric cancer cells. Methods SHH expression was assessed using immunohistochemistry and the results were compared with clinicopathologic parameters, including survival. Using gastric cancer cell lines, we measured SHH mRNA and protein expression, and studied the effects of SHH signaling on cell proliferation and SHH secretion. We also studied the effects of an inhibitor of PLC-γ1 on phosphorylation of phospholipase Cγ1 and extracellular signal-regulated kinases (ERK)1/2. Results SHH protein expression in gastric cancer tissue was significantly higher compared with that in normal gastric tissue (P < 0.001), and the increased expression was significantly associated with pT staging (P = 0.004), pN staging (P = 0.018), pM staging (P = 0.006), and pTNM staging (P < 0.001). In multivariate analyses, overall survival in gastric cancer was significantly shorter in cases with high SHH expression (HR = 1.734, 95 % CI: 1.109–2.713, P = 0.016). The AGS and SGC-7901 gastric cancer cell lines expressed SHH mRNA and protein. In these cell lines, SHH promoted carcinogenesis through activation of the PLCγ1-ERK1/2 pathway, resulting in increased cell proliferation and survival. Conclusions Increased SHH expression is associated with shorter survival in gastric cancer patients, and SHH could represent a useful biomarker or therapeutic target for this disease.